Validity Trainer Tool As Learning Media for Electric Power Distribution System - Andrian, Andrian; Ganefri, Ganefri; Sukardi, Sukardi (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Electric Power Distribution System Learning has demands for learning outcomes so that students understand the concept, and have basic knowledge and skills in various constructions of electric power distribution networks. This requires varied and more contextual learning methods and requires contextual learning media as well. The learning media used should be able to provide real experiences for students in simulating the electric power distribution system according to the concepts they are learning. However, the ability of students in the configuration of various distribution networks has problems because there is no suitable learning media. Therefore, it is necessary to develop a valid power distribution system trainer for use in learning. This study aims to produce a valid electric power distribution system trainer. This type of research is research & development (R&D) using the ADDIE model. Research is limited to the development stage (development). The validation test was carried out by 4 validators using an instrument in the form of a validation sheet. The results of the validation show that the electric power distribution system trainer developed is in the valid category, both for content quality aspects and objectives, instructional, and technical. This indicates that the trainer developed is appropriate for use in learning in order to test its effectiveness.